(untitled) - Doyle, Arthur Conan (Oxford, 2000)
This award-winning collection of adapted classic literature and original stories develops reading skills for low-beginning through advanced students.
Keywords: Reading comprehension,Short stories.,Đọc hiểu; Problems, exercises, etc.,Câu hỏi và bài tập